«Imperial consensus»: the last attempt of England to prevent disintegration of the British Empire - V Mitrofanovich Zabolotny (RUDN Journal of World History, 2012)
The article deals with the last period of the British Empire well known by the term «imperialism». After the Boer war Britain undertakes serious attempts to reform the failing Empire and to strengthen it by new and more attractive ideas of «imperial consensus». Exactly at that time the first institutions of the British Commonwealth of Nations came into being. There is no doubt that at this complicated period England has prepared reliable background for the future Commonwealth.